Knowledge and Utilization of Postnatal Care Services among Mothers Residing in a Community of Jhapa District - Dahal, Menuka; Subedi, Sabitra; Mandal, Punam Kumari; Silwal, Suvekshya (Journal of College of Medical Sciences-Nepal, 2022)
Introduction Postnatal care is the most important maternal health care intervention for prevention of impairments, disabilities and also reduction of maternal mortality. However, mothers often only seek postnatal care in the event of complications after birth. The aim of this study is to assess the knowledge and utilization of postnatal care services among mothers in a community at Buddhashanti, Jhapa. Methods A descriptive cross sectional research design was adopted. Sample was taken from married women in the reproductive age group, residing in Buddhashanti rural municipality of Jhapa District, who had a live baby less than 24 months old, attending immunization outreach clinics. Non-probability purposive sampling was used to collect data. The sample size was 104. Data were collected using a self-developed, semi-structured questionnaire through interview. Descriptive statistics such as frequency mean and standard deviation were used in the analysis of collected data. Association between dependent and independent variables was measured by using the Chi- square test. Results The finding of the study revealed that less than half (32.7%) of the mothers had good knowledge on postnatal care. Similarly, the majority (87.5%)of mothers had not utilized postnatal care services. Study revealed that level of knowledge had significant association with ethnicity, educational level of respondent and number of ANC visits with p- value 0.002, 0.038, 0.040 respectively. Furthermore, utilization of postnatal care had association with occupation of respondent and type of delivery (p- value<0.05). Conclusions This study showed that respondents had poor knowledge on postnatal care and the majority of respondents had not utilized postnatal care services. Study revealed that ethnicity; educational level of respondent and no. of ANC visit had association with level of knowledge. Furthermore, occupation of respondent and type of delivery had association with utilization of postnatal care.